The potential of overlooked material in museum repositories: Revisiting grave materials in Falbygden through multiproxy analyses - Blank, Malou; Tornberg, Anna; Mark, Chris (Danish Journal of Archaeology, 2025)
In this article we aim to highlight the potential of forgotten grave materials in our museum depositories for gaining insights into prehistoric life. By applying a multi-proxy approach to the skeletal remains of two graves of uncertain types from Falbygden in western Sweden, we were able to acquire new knowledge of burial practices, subsistence, health and mobility in Late Neolithic and Early Bronze Age communities. One of the studied graves proved to be the earliest attested gallery grave in the area, while the other is one of the few known graves from the first period of the Bronze Age. The results indicate that some overlooked excavated materials in our depositories might stem from certain time periods from which we think archaeological remains are lacking and/or from practices which are not fully understood. These remains may prove to be important for our understanding of prehistoric societies when thoroughly studied combining archaeological, osteological, biochemical and geochemical methods.